Computational study of productive and non-productive cycles in fluoroalkene metathesis - Rybáčková, Markéta; Hošek, Jan; Šimůnek, Ondřej; Kolaříková, Viola; Kvíčala, Jaroslav (Beilstein journal of organic chemistry, 2015)
A detailed DFT study of the mechanism of metathesis of fluoroethene, 1-fluoroethene, 1,1-difluoroethene, cis- and trans-1,2-difluoroethene, tetrafluoroethene and chlorotrifluoroethene catalysed with the Hoveyda-Grubbs 2(nd) generation catalyst was performed. It revealed that a successful metathesis of hydrofluoroethenes is hampered by a high preference for a non-productive catalytic cycle proceeding through a ruthenacyclobutane intermediate bearing fluorines in positions 2 and 4. Moreover, the calculations showed that the cross-metathesis of perfluoro- or perhaloalkenes should be a feasible process and that the metathesis is not very sensitive to stereochemical issues.
Keywords: DFT; computation; mechanism; alkene metathesis; productive cycle; fluoroalkene; non-productive cycle